2013
DOI: 10.1094/pdis-03-13-0230-re
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Pathogenicity of Fungal Pathogens Associated with Stem-End Rot of Avocado in California

Abstract: Stem-end rot of harvested avocado fruit commonly occurs wherever the crop is cultivated. Multiple fungal species have been described as causal agents. To determine the causal pathogens of stem-end rot in California, fungal isolations were conducted from symptomatic fruit, and fungi were identified by morphological and molecular techniques. In 2010 and 2011, a total of 177 isolates were recovered from 290 avocado fruit collected from seven orchards in one of the major avocado growing areas in Southern Californi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 16 publications
2
34
0
3
Order By: Relevance
“…were less virulent in our inoculation studies compared to N. parvum. The Diaporthe spp., were isolated exclusively from branch cankers, but are reported to cause avocado fruits disease elsewhere (Twizeyimana et al 2013). In this study, when Diaporthe spp.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…were less virulent in our inoculation studies compared to N. parvum. The Diaporthe spp., were isolated exclusively from branch cankers, but are reported to cause avocado fruits disease elsewhere (Twizeyimana et al 2013). In this study, when Diaporthe spp.…”
Section: Discussionmentioning
confidence: 76%
“…This fungus was recovered from all orchards sampled and was identified by comparing morphology and through phylogenetic analysis (Phillips et al 2013). Neofusicoccum parvum is reported to be a major stem canker and stem-end rot pathogen of avocado in California, Australia, New Zealand and South Africa (Darvas et al 1987;Hartill and Everett 2002;McDonald et al 2009;Twizeyimana et al 2013 (Ismail et al 2013, Phillips et al 2013. Indeed, this is the first report of N. parvum causing disease on avocado (branch canker and stem-end rot) in Italy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…and Fagus crenata B1 (Osono 2006), Colletotrichum gloeosporioides and Phomopsis sp. (Rivera-Vargas et al 2006;Twizeyimana et al 2013), and Table 5.1 listed some examples of phyllosphere fungal endophytes. Osono (2008) reported that endophytic Colletotrichum gloeosporioides and C. acutatum, and epiphytes Pestalotiopsis sp., Aureobasidium pullulans, Phoma sp., and Ramichloridium sp.…”
Section: Fungal Microbiota Of Phyllospherementioning
confidence: 99%